Lantana camara in the soil changes the fungal community structure and reduces impact of Meloidogyne javanica on mungbean - Shaukat, Ayed Shahid; Siddiqui, Imran Ali (Phytopathologia Mediterranea, 2001)
Changes in the fungal community resulting from nematode suppression were studied by comparing thenumber of fungal species in the soil and mungbean roots between soils with and without amendment with Lantanacamara. Addition of L. camara to the soil at 1% (w:w) significantly reduced the Meloidogyne javanica populationdensity in the soil and in the roots of mungbean, as well as subsequent root-knot infestation of mungbean, confirmingthat nematode suppressiveness was induced by this organic amendment. L. camara amendment was associated withan increase in fungal populations, especially those with nematicidal activity. The soil was probably the major sourceof fungal endophytes in mungbean roots since nearly all the endophytic fungi were also found in the soil. L. camaraamendedsoils contained several fungi that were not found in unamended soil, including an Acremonium sp., Aspergillusfumigatus, Drechslera australiensis, Fusarium culmorum, Penicillium notatum and Trichoderma viride.The fungi in the inner root tissues of mungbean growing in L. camara-amended soil included an Acremonium sp., F.solani, Macrophomina phaseolina, Penicillium sp., and Trichoderma viride. Only T. viride was not encountered inthe inner root tissues of mungbean in unamended soil. M. phaseolina and F. solani were isolated with relatively highfrequency from the inner root tissues of mungbean growing in unamended soils while the remaining endorhizal fungiwere more frequent in amended soils. M. phaseolina, though isolated extensively from the inner root tissues, eitherdid not occur in the soil or was not isolated by the soil dilution technique used. When fungi from soil amended with L.camara were tested for their nematicidal and hatch-inhibiting activity, Aspergillus niger produced the greatest nematodemortality, while T. viride caused the greatest inhibition of egg hatching of M. javanica.